2021
DOI: 10.5334/aogh.3060
|View full text |Cite
|
Sign up to set email alerts
|

The Rise in Cardiovascular Risk Factors and Chronic Diseases in Guyana: A Narrative Review

Abstract: Background: Guyana experiences health challenges related to both communicable and non-communicable diseases. Cardiovascular disease (CVD) is the most common non-communicable disease in Guyana. The main causes of the increased prevalence of non-communicable diseases are modifiable risk factors (e.g. obesity, hypertension, elevated cholesterol, unhealthy dietary patterns) and non-modifiable risk factors (e.g. age and genetics). Objective: The aim of this review is to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…For this reason, cardiovascular diseases are on the rise. In addition, these lifestyle changes increase exposure to other cardiovascular risk factors (e.g., diabetes, obesity, and hypertension) ( 29 ) . Despite public health policies to prevent and care for chronic conditions in Guyana, the widespread belief that chronic non-communicable diseases, like diabetes and cardiovascular diseases, are consequences inherent to the aging process hinders the prevention and management of these diseases ( 30 ) .…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, cardiovascular diseases are on the rise. In addition, these lifestyle changes increase exposure to other cardiovascular risk factors (e.g., diabetes, obesity, and hypertension) ( 29 ) . Despite public health policies to prevent and care for chronic conditions in Guyana, the widespread belief that chronic non-communicable diseases, like diabetes and cardiovascular diseases, are consequences inherent to the aging process hinders the prevention and management of these diseases ( 30 ) .…”
Section: Discussionmentioning
confidence: 99%
“…There have also been reports of a higher prevalence of diabetes and cardiovascular disease in people of South Asian ethnicity in Singapore, Fiji, and Guyana, although the number of studies has been fewer. [14][15][16][17][18] Elevated diabetes and cardiovascular risks in South Asians are derived from several nonmodifiable and modifiable risk factors (Figure 1).…”
Section: What Drives Vascular Disease and Ckd In South Asians?mentioning
confidence: 99%
“…During the last 10–15 years, the country has witnessed considerable progress in population health in terms of increased life expectancy, reduction in maternal and child mortality, greater access to healthcare services and availability of improved water and sanitation facilities ( 1 – 4 ). In parallel with these important achievements, the country is also experiencing a rapid rise in the burden of non-communicable diseases (NCDs) such as cardiovascular diseases, stroke, diabetes and cancer ( 5 7 ). As such, the country is undergoing a major epidemiological transition from infectious to chronic diseases characterized by changes in lifestyle-related behaviors such as unhealthy dietary behavior and increased consumption and tobacco and alcoholic products.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the country is undergoing a major epidemiological transition from infectious to chronic diseases characterized by changes in lifestyle-related behaviors such as unhealthy dietary behavior and increased consumption and tobacco and alcoholic products. In fact, Guyana has the highest rates of cardiovascular and ischemic heart disease-related deaths compared to other countries in the Americas, and also experienced a 32% rise in the prevalence of hypertension between 2007 and 2017 ( 5 ). Studies have shown that both alcohol and tobacco are major risk factors for NCDs ( 8 – 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation